Pinch Effort Variations With Torque, Shape And Size, Sensation And Technique - Poh, Kiat Ng; Saptari, Adi; Qiao, Hui Boon; Meng, Chauw Bee; Ka, Xuan Chai; Shiong, Lung Leh (Asian Network for Scientific Information, 2014)
-